Review: Antibacterial Activities of Various Parts of Mengkudu (Morinda citrifolia L.) Plants on Some Species of Bacteria - Barolym Tri Pamungkas; Moelyono Muktiwardojo; Tina Rostinawati (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2019)
The high incidence of infections and the increase in antibiotic resistance have become a global health concern. The emergence of strains of resistant bacteria has also encouraged the exploration of potential antibacterial agents, especially from natural sources. This review aims to provide information regarding the antibacterial activity of stems, leaves, fruits and seeds of mengkudu (M. citrifolia L,) in inhibiting various bacterial species. In this article review, online and offline literature were used. Online literature was obtained from local and international journals and scientific articles of the last 10 years, 2008-2018, which were obtained through direct search results online using online search engines namely Google and Google Scholar. Whereas the offline literature used is books and e-books. It is known that the root, stem, leaves, fruit, and seeds of mengkudu (M. citrifolia L,) with various solvents used can inhibit various species of bacteria with different diameter inhibition zones.